Whole chromosome painting in two populations of the weakly electric fish Gymnotus mamiraua (Teleostei, Gymnotiformes) - Ananda Marques Pety; Milla de Andrade Machado; Fernando Henrique Ramos Silva; Paula Pinto Rodrigues; Eliana Feldberg; Patricia Caroline Mary O’Brien; Malcolm Andrew Ferguson-Smith; Julio Cesar Pieczarka; Cleusa Yoshiko Nagamachi (Scientific Reports)
Abstract Techniques such as whole chromosome painting (WCP) have effectively expanded our understanding of the evolution and organization of the genome in fish, allowing us to obtain more detailed information about several evolutionary questions. The genus Gymnotus is the most cytogenetically studied among the Gymnotiformes, having a significant karyotypic diversity. Molecular cytogenetic studies in the genus Gymnotus show a dynamic reorganization in the karyotype, in addition to the presence of different sex chromosome systems. In this study, with whole chromosome probes from the karyotype of Gymnotus carapo orientalis sensu stricto cytotype 2n = 42, we analyzed the karyotype of Gymnotus mamiraua 2n = 54, from two localities, and compared with previous studies, to obtain a better understanding of the homologies and chromosomal differences among the species of this genus. The results shows both populations with no difference detected by chromosome painting, and overall, a larger number of signals were observed with the fluorescent probes, since GMA has a higher diploid number. Using chromosomal painting on a greater number of species will make it possible to construct a map of homologies between them that will help define the phylogeny of the group.